Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.2340/17453674.2023.11961
|View full text |Cite
|
Sign up to set email alerts
|

10-year evolution of day-case hip and knee arthroplasty: a Danish nationwide register study of 166,833 procedures from 2010 to 2020

Abstract: Background and purpose: No previous studies have investigated the use of day-case arthroplasty in Denmark on a national scale. We investigated the frequency of day-case surgery in total hip (THA), total knee (TKA), and unicompartmental knee arthroplasty (UKA) from 2010 to 2020 in Denmark.Patients and methods: Primary unilateral THAs, TKAs, and UKAs performed for osteoarthritis were identified in the Danish National Patient Register using procedural and diagnosis codes. Day-case surgery was defined as discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…While the shift towards ambulatory surgery is often stepwise [ 14 16 ], our institution faced a swift change in practice. Mitchell et al recently disseminated findings of a similar study, comparing the management evolution between 2019 and 2020 at a single centre in the United States [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the shift towards ambulatory surgery is often stepwise [ 14 16 ], our institution faced a swift change in practice. Mitchell et al recently disseminated findings of a similar study, comparing the management evolution between 2019 and 2020 at a single centre in the United States [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence suggesting the safety and efficacy of outpatient THR [ 9 12 ], with some groups reporting up to 75% utilisation of outpatient management [ 13 ]. While the transition to outpatient surgery typically involves a stepwise process amongst all stakeholders involved in patient care [ 14 16 ], the recent pandemic has necessitated rapid adaptation in practice.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Enhanced Recovery After Surgery (ERAS) guidelines are widely implemented in Denmark and half of the patients are discharged home the day after surgery. 1,2,19 Eligibility criteria: All eligibility criteria will be assessed at time of surgery. All adults (≥18 years old) who underwent elective, unilateral THA or TKA due to primary osteoarthritis between 1 January 2010 and 31…”
Section: Methodsmentioning
confidence: 99%
“…Previous single-center studies have shown the potential to discharge patients on the day of surgery after primary total hip arthroplasty (THA), total knee arthroplasty (TKA), and unicompartmental knee arthroplasty (UKA) [ 7 - 10 ]. Although selective use of outpatient surgery in individual centers has been shown to be feasible, the use of outpatient surgery on a national level is low [ 11 , 12 ]. Therefore, the study group designed a detailed protocol for the implementation of outpatient surgery in a multicenter collaboration across all regions in Denmark [ 13 ].…”
mentioning
confidence: 99%